Efficacy and safety of first-line targeted and immunotherapy for metastatic colorectal cancer: a network meta-analysis - Huo, Liman; Yue, Hongyu; Yang, Ruixia; Sun, Xiaoli; Wang, Ziyue; Liu, Hong; Liu, Jiang; Feng, Rui; Liang, Ping (Frontiers in Immunology, 2025)
BackgroundAs targeted therapies and immunotherapy become increasingly prevalent in treating metastatic colorectal cancer (mCRC), comparative analyses are essential to determine the most effective and safe treatment combinations. This study aims to compare and rank the efficacy and safety profiles of first-line systemic treatments for mCRC.MethodsThis network meta-analysis was conducted in compliance with PRISMA guidelines, reviewing randomized controlled trials from PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov through March 2024. A network meta-analysis is conducted using a Bayesian random effects mode. After the data was extracted, data analysis was conducted in gemtc R. The primary outcomes measured were overall survival (OS), progression-free survival (PFS), and the incidence of adverse events (AEs) graded ≥3.The Cochrane risk-of-bias assessment tool was used to evaluate the quality of each study.ResultsA total of 61 RCTs involving 20,579 patients were included. The results showed that FOLFOXIRI combined with bevacizumab and atezolizumab significantly improved PFS and OS, with HRs for PFS and OS of (HR:0.19, 95% CI: 0.11–0.33), (HR:0.48, 95% CI: 0.30–0.78), respectively. The incidence of ≥ Grade 3 AEs was high, but no new fatal treatment-related AEs were observed, and the safety of this regimen was manageable. FOLFOXIRI in combination with anti-EGFR monoclonal antibody regimens showed significant PFS and OS improvements in the RAS/BRAF wild-type subgroup. For the subgroup of patients aged ≥ 70 years, thetrifluorouridine-tipiracil plus bevacizumab regimen also had some advantage in PFS and OS. Although the incidence of Grade ≥ 3 AEs was higher, the incidence of AEs was similar across age groups and well tolerated in this regimen, and it was more suitable for elderly cancer patients.DiscussionThese findings underscore the importance of integrating targeted drugs and immunotherapy in first-line mCRC treatments, highlighting significant differences in efficacy and safety profiles that can guide therapeutic decisions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024604107, identifier CRD42024604107.